Optimization of process parameters for TC11 alloy via tailoring scanning strategy in laser powder bed fusion - Shu, Chang; Zheng, Zhiyu; Lei, Peiran; Xu, Haijie; Shu, Xuedao; Essa, Khamis (Frontiers of materials science, 2024)
TC11, with a nominal composition of Ti–6.5Al–3.5Mo–1.5Zr–0.3Si, is the preferred material for engine blisk due to its high-performance dual-phase titanium alloy, effectively enhancing engine aerodynamic efficiency and service reliability. However, in laser powder bed fusion (L-PBF) of TC11, challenges such as inadequate defect control, inconsistent part quality, and limited optimization of key processing parameters hinder the process reliability and scalability. In this study, computational fluid dynamics (CFD) was used to simulate the L-PBF process, while design of experiments (DoE) was applied to analyze the effect of process parameters and determine the optimal process settings. Laser power was found to have the greatest impact on porosity. The optimal process parameters are 170 W laser power, 1100 mm·s −1 scanning speed, and 0.1 mm hatch spacing. Stripe, line, and chessboard scanning strategies were implemented using the optimal process parameters. The stripe scanning strategy has ∼33% (∼400 MPa) greater tensile strength over the line scanning strategy and ∼12% (∼170 MPa) over the chessboard scanning strategy. This research provides technical support for obtaining high-performance TC11 blisks.